Women’s Entrepreneurship in the context of problems, characteristics and reasons - Burcu Turan Torun (Sakarya Üniversitesi İşletme Enstitüsü Dergisi)
In this study, women entrepreneurship is discussed from various perspectives. The reasons that lead women to become entrepreneurs, the problems faced during and after establishing the business, the characteristics of women entrepreneurs, women's thoughts about entrepreneurship and their thoughts on the comparison of male-female entrepreneurship are discussed. This study was conducted with women who are registered with Van Chamber of Commerce and Industry. Problems experienced by entrepreneurial women, the advantages and disadvantages they faced were tried to be revealed through a semi-structured interview form. Unlike other provinces, female participants interviewed within the scope of the research are officially registered with the Chamber of Commerce. After the literature review in the study, what entrepreneur women experience while continuing their business life has been revealed within the framework of Van province. At the end of the study, it was seen that material and moral problems are important in women's entrepreneurship. It has been revealed that self-confidence has an important place in women entrepreneurs. Some women stated that they were better than men in entrepreneurship, while others stated that men were better in this regard.